Impaired periodontium and temporomandibular joints in TNF-α transgenic mice - Dobsak, Toni; Heimel, Patrick; Tangl, Stefan; Schwarze, Uwe Y.; Schett, Georg; Gruber, Reinhard (Journal of Clinical Periodontology, 2017)
TNF-? is a pathological factor causing the characteristic symptoms of periodontal disease and rheumatoid arthritis. In this study we describe the phenotypes of human tumor necrosis factor (TNF)-? transgenic mice (hTNFtg) with respect to their periodontium and the temporomandibular joint (TMJ).Periodontal structures, TMJ, and skull shape of hTNFtg mice and wild-type (WT) littermates were assessed by micro computed tomography, automated segmentation, geometric morphometrics and histologic ground sections.We show that hTNFtg mice have an eroded lamina dura and reduced periodontal ligament space compared to (WT) littermates. Transgenic mice further exhibit severe destruction of the TMJ. Geometric morphometrics revealed that hTNFtg mice have a more laterally positioned TMJ with a concomitantly enlarged zygomatic process. Mandibular and maxillary teeth occluded properly.Our findings suggest that chronic inflammation in hTNFtg mice causes destructive changes of the periodontium and the TMJ. This article is protected by copyright. All rights reserved.
EVALuna2:13443